Caracterização genotípica de Streptococcus mutans isolados da placa dental de pacientes jovens com histórico de infarto agudo do miocárdio: frequência e relação com o risco cardiovascular - Rocha, Francisco Ruliglésio (2020)
The bacterium Streptococcus mutans is widely associated to dental caries and it is classified into four clinical serotypes (c, e, f and k). Rare serotypes (e, f and k), multiple serotypes and its collagen-binding protein genes (cnm and cbm) have been associated to cardiovascular diseases. However the prevalence of S. mutans, the serotypes and the collagen-binding protein genes, as well as its relation with dental caries and acute myocardial infarction (AMI), are not known in Brazil. The present study investigated the prevalence of S. mutans, serotypes, cnm and cbm genes in dental plaque and its relation with dental caries and AMI from 31 infarcted adult patients at age before 50 years old, with 17 volunteers without history of heart disease as a control. The assessment of the presence and carious lesion severity was performed using the International Caries Detection and Assessment System (ICDAS). Lipid and glycemic profiles were accessed in serum by colorimetric enzymatic methods. A total of 5-15 isolates with S. mutans morphology were obtained from each dental plaque samples in Mitis Salivarius Bacitracin (MSB) agar culture medium. The DNA from dental plaque samples and bacterial isolates was extracted and analyzed for identification of S. mutans by the PCR technique. Positive samples were analyzed to determine serotypes and identify cnm and cbm genes. It was found that S. mutans was identified in 22.6% (7/31) and 11.8% (2/17) of the analysed samples from infarcted and controls, respectively. Serotyping of dental plaque samples and bacterial isolates from infarcted patients with S. mutans showed that serotype c was the most prevalent (57.1%; 4/7), followed by e (42.9%; 3/7) and k (14.3%; 1/7). Only the serotype c was identified in samples from the control group (100%; 2/2). Rare serotypes (e or k) and multiple serotypes (c and k) were identified only in infarcted patients. The cnm and cbm genes were not found in the analyzed samples. The presence of S. mutans, regardless of serotype, was not associated to dental caries in infarcted (p = 0.853) and controls (p = 0.787). Regression analysis showed that individuals with cholesterol levels below 190 mg/dL and without S. mutans presented a 47.4% lower probability of infarction (OR = 0.474; 95% CI = 0.956 - 0.992). This is the first study to report the prevalence of S. mutans serotypes in cardiac patients in Brazil. The identification of rare serotypes in infarcted patients, as well as the presence of multiple serotypes in the dental plaque of one of these patients, alert to the need for more extensive studies in population at risk for cardiovascular diseases. Normal cholesterol levels in non-carriers of S. mutans may be associated with a lower probability of infarction.